Flaxseed supplementation in buffaloes attenuates plasma PGF2Î± concentrations during last quarter of estrus cycle - NAZIR, G; GHUMAN, S P S; HONPARKHE, M; DHALIWAL, G S; SHARMA, R; PHAWA, B; HASSAN, N; HUSSAIN, S A (The Indian Journal of Animal Sciences, 2013)
The present study was designed to test the effect of flaxseed supplementation on luteal phase plasma PGF2Î±. The study was conducted on 6 lactating Murrah buffaloes used as self-control and the experiment was divided into 2 periods; pre-supplementation and supplementation period. During pre-supplementation period, all the buffaloes were synchronized using Ovsynch+CIDR protocol. On day 15 of synchronized estrous cycle, animals were subjected to oxytocin challenge test and blood samples were collected at 15 min interval starting 1 h before till 4 h after oxytocin challenge. Thereafter, same buffaloes were supplemented with flaxseed (300g/100 kg bwt/day) for 60 days. After 35 days of supplementation, buffaloes were again synchronized using same protocol and were subjected to oxytocin challenge test and similar blood sampling protocol on day 15 of synchronized cycle as during pre-supplementation period. Mean plasma PGF2Î±-metabolite was lower during supplementation period compared to pre-supplementation period. However, oxytocin failed to have any impact on plasma PGFM concentrations both during pre-supplementation and flaxseed supplementation period.